Strategi Pengembangan Benih Padi Untuk Mendukung Ketahanan Pangan di CV Priangan Timur Seed Community (PTSC) Kabupaten Ciamis - Nuraini, Candra; Mutolib, Abdul; Fajria, Novia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
ABSTRACT Food security is a priority in national development, and developing high-quality rice seeds is one of the main strategies to achieve it. This study was conducted to formulate strategies for developing rice seeds at CV PTSC to support food security. The research was carried out at CV PTSC in Ciamis Regency using a purposive sampling technique, considering that this company is the sole producer of rice seeds in the Priangan Timur region. The data used in this study comprised primary and secondary data collected through in-depth interviews with key stakeholders. Respondents included the management of CV PTSC, partners (traders and farmers), academics, and government institutions such as the Agricultural Office and the Seed Supervision and Certification Center (BPSBTPH) of West Java Province. The research employed a case study method, with data analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to identify internal and external factors affecting business development. The Analytic Hierarchy Process (AHP) was applied to determine the priority of strategies based on the weight of each factor.The results indicated that CV PTSC has significant potential to leverage internal strengths such as technological innovation and an extensive distribution network while addressing external threats like climate change and market competition. Based on the AHP analysis, the recommended priority strategies are as follows: first, expanding partnerships from upstream to downstream to support the production and marketing of seeds, with a weight of 0.99; second, Promoting digital marketing and collaborating with relevant institutions to enhance seed marketing, with a weight of 0.96. Third, seed quality in terms of cultivation practices and certification by seed certification agencies should be improved, with a weight of 0.92.